Unbundling Institutions for External Finance : Worldwide Firm-Level Evidence - Knack, Steve; Xu, Lixin Colin (World Bank, Washington, DC, 2015)
The empirical literature on institutions and development has been challenged on grounds of reverse causality, measurement error in institutional indicators, and heterogeneity. This paper uses firm-level data across countries to confront these challenges. Instead of analyzing ultimate outcomes, such as income levels where institutional quality is likely endogenous, the focus is on firm-level external finance. Moreover, institutions are “unbundled” to explore how various types of institutions affect external finance differently. The paper documents that micro firms have significantly less access to external finance than small and medium firms. General financial development and contracting institutions that facilitate transactions between private parties exert little effect, on average, on firms’ access to external finance. In contrast, property rights institutions that constrain political and economic elites exhibit stronger positive association with access to external finance. The analysis finds evidence of attenuation bias associated with error in measuring institutions. For leveling the playing field between elite and non-elite firms (as proxied by firm size) in their access to external finance, property rights institutions also figure more prominently—with an important exception for the information environment, a component of contracting institutions. The results indicate that a specific channel through which development is affected more by property rights institutions rather than contracting institutions is external financing for firms.